PERANCANGAN NAKAS MULTIFUNGSI HIDDEN DRAWER DENGAN MIX MATERIAL - Etruly, Niki; Yusuf, Ahmad (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2024)
In the development of minimalist and modern interior design, space limitations are a major problem, especially in creating a multifunctional bedroom design. The bedroom is not only used as a place to rest, but is used as a place for storage, work, and other activities, so it requires several functional and efficient design solutions. One of the products developed is a multifunctional nightstand that has been equipped with more storage, hidden drawers, and a table top that can be directed to the bed. This product is designed using a combination of teak wood, plywood, and veneer with natural finishing, giving a natural and aesthetic impression. Research on this product uses quantitative method research through filling out questionnaires to respondents. The process of designing this product follows by using the design thinking method which involves five stages, namely the empathize, define, ideate, prototype, and test stages. The final result is a prototype of a multifunctional nightstand that has been equipped with woven rattan to add an aesthetic impression. The data shows that this product obtained score of 91.05%, which shows that this product is very attractive and meets the needs as a creative solution to the problem of limited space.